Promoting Adult Hippocampal Neurogenesis: A Novel Strategy for Antidepressant Drug Screening - Yan, H.-C.; Cao, X.; Gao, T.-M.; Zhu, X.-H. (Current Medicinal Chemistry, 2011)
Major depression is a common mood disorder that affects overall health; currently, almost all of the available antidepressants have the same core mechanisms of action through promotion of serotonin or noradrenaline function in the brain. The major limitation of today's antidepressants is that chronic treatment (3 - 6 weeks) is required before a therapeutic benefit is achieved. More effective and faster treatments for depression are needed. Adult neurogenesis is the birth of new neurons, which continues postnatally and into adulthood in the brains of multiple species, including humans. Recently, a large body of evidence gives rise to the hypothesis that the antidepressant effect and increases in adult hippocampal neurogenesis may be causally related. Multiple classes of antidepressants increase hippocampal neurogenesis in a chronic, but not acute, time course. This effect corresponds to the therapeutic time lag associated with current antidepressants. In addition, antidepressants are not effective in behavioral models of depression when hippocampal neurogenesis is prevented. This review examines the current understanding of adult neurogenesis and the evidence of the causal relationship between antidepressant effects and adult hippocampal neurogenesis. We also present our recent research findings, which support a promising strategy for enhancing adult hippocampal neurogenesis that might be a new approach for the development of novel antidepressants.
Keywords: GABA